STUDENTS’ LANGUAGE AWARENESS ON LINGUISTICS PROBLEMS DURING NEGOTIATION OF MEANING IN PAIR WORK DISCUSSION. - Flora Flora (Universitas Muria Kudus, 2021)
The objectives of this study are :1) to describe linguistics problems produced by the students during the negotiation of meaning in pair work discussion, and 2) to describe the students’ language awareness (willingness and unwillingness to correct the linguistics problems). This study applied descriptive quantitative design and the subjects are 3 pairs consisting of high-high (H-H) learner, high and low (H-L) learner and low- low (L-L) learner. All of them are the fourth semester students of English department of teachers training faculty of Lampung University in academic 2018/2019. Each pair was given a topic (chosing 5 personality traits that a teacher should have). Each pair discussed the topic and during the discussion, all their utterances were recorded, transcribed and were analyzed based on relevant theories. The results show that each pair produced linguistics problems, such as grammatical and vocabulary. Most of the learners, especially H-L and L-L are not aware of linguistics problems because they focus more on the message across. Eventhough some of the pairs are aware of linguistics problems and are willing to correct them, it does not guarantee that the input can be internalized by their pairs since they focus more on meaning during the interaction. Therefore, it is suggested further researchers investigate this phenomena.